HUBUNGAN FAKTOR KEJADIAN HIPERTENSI PADA LANSIA DI WILAYAH KERJA PUSKESMAS HALONG - Ivy Violan Lawalata; Bellytra Talarima; Dolvina Sahulatta (MOLUCCAS HEALTH JOURNAL, 2021)
Hypertension or high blood pressure is the cause of death and high illness. Hypertension as a chronic disease is influenced by several factors. The risk factors for hypertension are divided into non-modifiable risk factors and modifiable risk factors. The purpose of this study was to determine the factors associated with the incidence of hypertension in the elderly in the working area of the Halong Public Health Center. This study uses an analytical survey method with a cross sectional research design. The sample size was 73 people with purposive sampling technique. The results of the physical activity test with the incidence of hypertension in the elderly obtained a p-value=0.03, smoking habits p-value=0.04, genetic factors p-value=0.03, obesity p-value=0.00. This it can be concluded that there is a relationship between physical activity, smoking habits, genetic factors and obesity with the incidence of hypertension in the elderly in the working area of the Halong Public Health Center. This research is expected to be an illustration to the public to prevent hypertension